Impact Of Soil Dwelling Entomopathogenic Nematodes, Recovered From The Soil Of Uttar Pradesh (India), On Cotton Bollworm Helicoverpa Armigera (Hübner) (Lepidoptera: Noctuidae) (Applied Biological Research, 2017)
High mobility, facultative diapause as pupae, rapid generation turnover,  fecundity and ability to develop resistance against insecticides, make the  management of Helicoverpa armigera very difficult. Entomopathogenic  nematodes (EPNs) have wide host range and possess several positive  attributes which make them one of the promising biocontrol agent. To  establish their possible role in insect pest management, 12 EPN isolates,  recovered from five districts of Uttar Pradesh (India), were used to test  their virulence and biotic potential against the larvae of H. armigera.  Based on morpho-molecular study they were identified as isolates of  Steinernema abbasi, S. siamkayai and Heterorhabditis indica. All the tested  isolates were virulent to kill H. armigera larvae within 24 to 60 h even at  lowest dose (25 IJs larva-1) and produced quantifiable infective juveniles.  indica isolate CH3 produced highest number of IJs (115.7±5 × 103 IJs larva-1), followed by S. abbasi isolate CS5 (100±8.5 × 103 IJs larva-1); whereas lowest was recorded from S. abbasi isolate CS3 (26.9±3×103 IJs larva-1). Cent percent mortality with short LT50 values ranging from 17.02 to 44.77 h at all concentrations proved the pathogenicity of allied steinernematids and heterorhabditids against H. armigera under laboratory conditions.
Keywords: Entomopathogenic nematodes; Helicoverpa armigera Steinernema abbasi; S. siamkayai; Heterorhabditis indica; virulence; progeny production